Developing a temporary external fixator (TEF) for mandibular reconstruction using two-phase QFD and TRIZ approach - Rungsan Chaiyachet,; Apichart Boonma,; Teerawat Paipongna, (Penerbit Universiti Kebangsaan Malaysia, 2024)
A temporary external fixator (TEF) is a device used to bridge resection defects after sequestrectomy and before secondary mandibular reconstruction surgery. A well-designed TEF should be customizable and adjustable to accommodate individual patient needs. This study developed a TEF for mandibular reconstruction using the quality function deployment (QFD) and the theory of inventive problem-solving (TRIZ). Customer needs (CNs) were investigated from literature reviews and a survey. Subsequently, a questionnaire was developed, refined, and delivered to 22 experts to identify the essential principles of TEF. Afterwards, the QFD priorities were analyzed based on the acquired CNs and technical requirements (TRs), and the top priorities were found to be safety and adequate operational space. The guidelines for developing a TEF with TRIZ were established as follows: First, using carbon fiber epoxy composite and Ti-6Al-4V as the material for TEFs is recommended Second, permanent magnet should be inserted into the clamp lock bolts to prevent them from falling off during surgery. Last, replacing one Schanz screw with three Bicortical screws is recommended for the fixator pins. Additionally, it was also found that changing the screw size from 2.5–4.0 mm to 2.0–2.4 mm could reduce hole defects in the mandible.